ANALISIS PRODUKTIVITAS TENAGA KERJA UNTUK PEKERJAAN PONDASI DAN SLOOF PROYEK PEMBANGUNAN PERUMAHAN TALAGO GREEN ASRI KABUPATEN AGAM - Wahyudi, Sepri; Lalan, Helny; Hotter, Robby; Midya Octavia, Dyla (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
General development in the province of Western Sumatra has shown a fairly good and rapid improvement. It can be seen in one of the districts of Agam district which is located in the district of Basung Lubuk which is the construction of subsidized housing. In the development of the workforce in the construction industry is an important factor in measuring the performance of a company. Employee productivity is one of the factors affecting the success of the project. In this case, how much productivity can improve the quality of work. In this research use mixed methods, qualitative and quantitative. By taking concepts based on experience that often happens in the field and is general. Types of jobs observed are foundation and sloof jobs. Data collection techniques using field survey data, calculating jobs and documentation. The results of the data analysis are presented in the form of graphs and presentation tables. Based on the results of the research, then it can be said that the work of foundation and sloof was productive, with the analysis of the data of LUR all labor earned more than 50%. The highest productivity result (LUR) on the job of anstampang was of 78,575%, work of sand grinding under the foundation was of 75,975%, then the pair of stone foundation times of 67,045%, and the grinding of the ground was of 66,73%. The highest yield of productivity (LUR) in cutting was 70.11%, then cutting work was 64.84%, and casting of K-175 concrete sloof was 58.89%. Keywords: Productivity, Labor Utilization Rate (LUR), Funding, Sloof